Застосування пристроїв звуження для обліку природного газу на газонаповнювальних станціях - Матіко, Федір (Видавництво Національного університету «Львівська політехніка», 2001)
Article contains the analysis of application possibility of the spesial restrictions for measurement of the flow rate and quantity of natural gas when filling the car gas-cylinders at compressor stations.